Gender, marriage, and the dynamic of (im)mobility in the mid-Western hills of Nepal - Zharkevich, I (Taylor and Francis, 2019)
This paper explores the relationship between gender, marriage, and (im)mobility in rural hilly areas of mid-Western Nepal, showing how (1) the mobility of men is predicated on the ‘immobility’ of women, with marriage being key to the gendered dynamic of (im)mobility, (2) how the construction of hegemonic masculinity, exemplified by a figure of a successful international migrant, is inseparable from an ideal of femininity vested in the figure of a virtuous domesticated housewife. Examining different scales of mobility, the paper cautions against posing a rigid dichotomy between ‘mobile men’ and ‘immobile’ women, illustrating that the ‘left behind’ wives experience an impressive degree of everyday mobility in contrast to their internationally mobile husbands.